2005
DOI: 10.1093/brain/awh665
|View full text |Cite
|
Sign up to set email alerts
|

Silent event-related fMRI reveals deficient motor and enhanced somatosensory activation in orofacial dystonia

Abstract: Previous studies showed cortical dysfunction and impaired sensorimotor integration in primary generalized and focal hand dystonia. We used a whistling task and silent event-related fMRI to investigate functional changes in patients with blepharospasm and patients with a combination of blepharospasm and oromandibular dystonia (Meige's syndrome). Whistling served as a model for a skilful orofacial movement with a high demand on sensorimotor integration. It allowed us to study the oromandibular motor system that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 59 publications
8
106
1
5
Order By: Relevance
“…This result contrasts with the hypothesis that plastic changes in the frontal lobe following focal dystonia would be associated with impaired executive function in these patients 19 .…”
Section: Discussioncontrasting
confidence: 89%
“…This result contrasts with the hypothesis that plastic changes in the frontal lobe following focal dystonia would be associated with impaired executive function in these patients 19 .…”
Section: Discussioncontrasting
confidence: 89%
“…These observations may suggest that abnormal sensory inputs coming to SMA neurons participate in the development of dystonia. Like SMA, the dorsal premotor cortex (PMd) is a part of motor cortex generally considered to be relevant to the planning, selection and execution of motor actions [31] as well as to sensorimotor integration in normals [6]. In generalized and focal dystonia patients, PET studies have reported hyperactive PMd and hypoactive M1 during movement compared to normals [32].…”
Section: Bont-a Treatment Effectmentioning
confidence: 99%
“…Differences among task conditions, including testing of dystonia-affected and unaffected body parts can partly explain this variance. It is also a matter of debate whether different types of primary dystonias share identical pathophysiological traits [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, reduced sensorimotor activation also may occur during dystonic movements (165,166). The abnormal fMRI signals for representation of digits in the primary sensory cortex (107,108) or other body parts in the basal ganglia (171) have been interpreted as a loss of neuronal selectivity.…”
Section: Wwwintechopencommentioning
confidence: 99%